POLICY NETWORK MANAGEMENT IN TOURISM SECTOR POLICY - Rizky Ilhami (Sean Institute, 2023)
As one of the sectors that is important for a country's economic growth, tourism requires a strong and well-coordinated policy framework to ensure sustainable growth and sustainable development. This research discusses the importance of policy network management in developing and implementing effective policies in the tourism sector. This research uses a qualitative approach with descriptive methods. The results of this research show that policy networks management has a crucial role in managing the complex tourism sector. By considering the complexity and dynamics involving multiple stakeholders, this research highlights the importance of effective management to resolve conflict, facilitate coordination, build trust, and increase active participation. By implementing an inclusive and collaborative approach, policy networks management can create a conducive environment for sustainable tourism development, provide a satisfying tourist experience, and provide a significant positive impact on local communities and the environment. Thus, this conclusion provides important insights for practitioners and policy makers in managing the tourism sector holistically and sustainably.